Logistics innovation and integration: Impact on supply chain adaptability - Sara Siddig Ali Abdalla (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: This study investigates the relationships among innovation by logistics services provider (LSP), user's supply chain (SC) adaptability, and the level of the user-provider relationship integration. Using low integrated, standard contractual relationships as a reference group, this study assesses how moderately integrated partnerships and highly integrated strategic relationships moderate the impact of LSP's innovation on the user's SC adaptability. Methodology: Moderated partial least squares structural equation modeling (PLS-SEM) was performed on survey data collected from 48 Sudanese companies. Findings: The findings revealed that innovation by LSPs had the greatest positive impact on SC adaptability in firms maintaining a moderate level of logistics integration. Interestingly, firms highly integrated with their LSPs witnessed a reduced effect of logistics innovation on their SC adaptability. In other words, while user-provider partnerships reinforced the impact of LSPs' innovation on user's SC adaptability, strategic relationships weakened this impact. Originality: Extant literature advocates fully integrating with LSPs to build a responsive, efficient SC. Nevertheless, the complexities of managing a highly integrated relationship with LSPs may pose challenges that exceed the expected benefits of such relationships. This study provides empirical evidence that moderate, rather than full, integration with LSPs may yield greater benefits for the users of logistics services.
urn:nbn:de:gbv:830-882.0161667; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Innovation Management; Technology management